New party parliamentary entry in Western Europe, 1960-2010 - Niklas Bolin (European Journal of Government and Economics (EJGE), 2014)
Although the number of studies of new political parties is gradually increasing, we still lack a comprehensive understanding of when new parties manage to enter national parliaments. The objective of this article is to explain the circumstances under which new parties enter national parliaments for the first time. Unlike earlier research, this study does not focus on individual party families. Instead, generally applicable explanations are sought. This is achieved through an examination of the importance of the political opportunity structure, that is, the external environment new parties face in their quest for parliamentary representation. Using data collected for 18 Western European countries for the period 1960-2010, the analysis shows that institutional factors are important to understand new party parliamentary entry. The sociological factors analysed in the study, however, do not seem to be of equal importance.
Keywords: 330; new parties; Western Europe; institutions; representation; political opportunity structure